Association of Blood Pressure Classification Using the 2017 American College of Cardiology/American Heart Association Blood Pressure Guideline With Risk of Heart Failure and Atrial Fibrillation. Issue 23 (22nd April 2021) - Kaneko, Hidehiro; Yano, Yuichiro; Itoh, Hidetaka; Morita, Kojiro; Kiriyama, Hiroyuki; Kamon, Tatsuya; Fujiu, Katsuhito; Michihata, Nobuaki; Jo, Taisuke; Takeda, Norifumi; Morita, Hiroyuki; Node, Koichi; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Heart failure (HF) and atrial fibrillation (AF) are growing in prevalence worldwide. Few studies have assessed to what extent stage 1 hypertension in the 2017 American College of Cardiology/American Heart Association blood pressure (BP) guidelines is associated with incident HF and AF. Methods: Analyses were conducted with a nationwide health claims database collected in the JMDC Claims Database between 2005 and 2018 (n=2 196 437; mean age, 44.0±10.9 years; 58.4% men). No participants were taking antihypertensive medication or had a known history of cardiovascular disease. Each participant was categorized as having normal BP (systolic BP <120 mm Hg and diastolic BP <80 mm Hg; n=1 155 885), elevated BP (systolic BP 120–129 mm Hg and diastolic BP <80 mm Hg; n=337 390), stage 1 hypertension (systolic BP 130–139 mm Hg or diastolic BP 80–89 mm Hg; n=459 820), or stage 2 hypertension (systolic BP ≥140 mm Hg or diastolic BP ≥90 mm Hg; n=243 342). Using Cox proportional hazards models, we identified associations between BP groups and HF/AF events. We also calculated the population attributable fractions to estimate the proportion of HF and AF events that would be preventable if participants with stage 1 and stage 2 hypertension were to have normal BP. Results: Over a mean follow-up of 1112±854 days, 28 056 incident HF and 7774 incident AF events occurred. After multivariable adjustment, hazard ratios for HF and AF events were 1.10 (95% CI, 1.05–1.15) and 1.07 (95% CI, 0.99–1.17), respectively, for elevated BP; 1.30 (95% CI, 1.26–1.35) and 1.21 (95% CI, 1.13–1.29), respectively, for stage 1 hypertension; and 2.05 (95% CI, 1.97–2.13) and 1.52 (95% CI, 1.41–1.64), respectively, for stage 2 hypertension versus normal BP. Population attributable fractions for HF associated with stage 1 and stage 2 hypertension were 23.2% (95% CI, 20.3%–26.0%) and 51.2% (95% CI, 49.2%–53.1%), respectively. The population attributable fractions for AF associated with stage 1 and stage 2 hypertension were 17.4% (95% CI, 11.5%–22.9%) and 34.3% (95% CI, 29.1%–39.2%), respectively. Conclusions: Both stage 1 hypertension and stage 2 hypertension were associated with a greater incidence of HF and AF in the general population. The American College of Cardiology/American Heart Association BP classification system may help identify adults at higher risk for HF and AF events.